Numerical Investigation of the Combustion in an Improved Microcombustion Chamber with Rib - Hai Chen; Wei-qiang Liu (Journal of Chemistry)
This study proposes an improved microcombustor with a rectangular rib to improve the temperature level of the combustor wall. Moreover, the OH mass fraction, temperature distribution, and outer wall temperature of the original and improved combustors of premixed hydrogen/air flames are numerically investigated under various inlet velocities and equivalence ratios. Results show that the improved microcombustor enhances heat transfer between the mixture and wall because its recirculation zone is larger than that of the original, thereby resulting in high wall temperature. Conversely, thermal resistance in the horizontal direction increases with upstream and downstream step lengths. Consequently, the outer wall temperature decreases with step length in the improved combustor. A high equivalence ratio (e.g., 0.6) may result in the destruction of the combustor because the wall temperature has exceeded the acceptable temperature of wall material quartz. Therefore, the improved microcombustor is recommended for micro-thermo-photovoltaic systems.